UTILIZATION OF ELECTRIC PULSED POWER ON FRUITING OF EDIBLE MUSHROOMS - Shoji Ohga (Central Laboratory for Genetic Resource and Molecular Biology, Faculty of Agriculture, Udayana University in cooperation with Asia-Oceania Bioscience and Biotechnology Consortium (AOBBC), 2012)
Eff ect of pulsed power was investigated on fruit body formation of 10 edible mushrooms, Lentinula edodes,Glifola frondosa, Pholiota nameko, Flammulina velutipes, Hypsizygus marmoreus, Pleurotus ostreatus, Pleurotuseryngii, Pleurotus abalones, Agrocybe cylindracea and Sparassis crispa. Pulsed power of 100-170 kV was directlycharged to the substrate just before fructifi cation. The eff ect of the pulsed power resulted to promote for 10edible mushrooms fructifi cation. The treatment especially stimulated the fructifi cation on Pleurotus species.